An assessment of the effectiveness of mechanical and chemical cleaning of Essix orthodontic retainer. (June 2014) - Chang, Chiew Sinn; Al-Awadi, Sarah; Ready, Derren; Noar, Joseph
Abstract : Objectives: To determine the effectiveness of mechanical and chemical cleaning on the removal of microorganisms from Essix orthodontic retainers.Design: In vitro laboratory study.Setting: Department of Orthodontics and Microbiology, Eastman Dental Institute, University College London, UK.Methods: Study 1: 120 Essix retainers were divided into four cleaning groups. The effectiveness of each cleaning method to remove a single species biofilm of Streptococcus mutans from the retainer was assessed. Study 2: 140 Essix retainers were divided into four study groups (brushing with fluoride toothpaste, chlorhexidine gel, immersion in chlorhexidine solution only and a control) to investigate the chemical and mechanical cleaning of the multispecies biolfilm of ( Streptococcus sanguis, Actinomyces naeslundii, methicillin-resistant Staphylococcus aureus and Candida albicans ).Relevant results: In study 1, brushing with toothpaste resulted in 99% reduction of Streptococcus mutans. In study 2, all three cleaning methods recorded similarly statistically significant reductions in colony forming units per millilitre compared to the control. There were no statistically significant differences between any of the cleaning groups for any of the microorganisms except MRSA-16 . For MRSA-16, chlorhexidine mouthwash and gel were significantly more potent in eliminating the microorganism than the fluoride toothpaste.Conclusions: All three cleaning methods effectively removed 99% of microorganisms from the Essix retainers. Brushing with fluoride toothpaste can therefore be confirmed as an effective method for cleaning retainers in most circumstances. The use of chlorhexidine gel or mouthwash is recommended in patients where bacterial infection has to be avoided due to immunosuppression or other reasons.